Pengaruh DER, ROA, SIZE, EPS, cash position dan TATO terhadap DPR perusahaan manufaktur Periode 2016-2019 - Nurul Hasanah Harahap, Qori; Br Situmorang, Monika; Karina Br Karo, Fristalia; Hayati, Keumala (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study is to examine the effect of DER, ROA, Firm Size, EPS, Cash Position, and Total Asset Turnover using the t-test and F test. This study uses quantitative descriptive. The number of manufacturing companies used as a population is 169 companies selected based on purposive sampling obtained a sample of 54 companies. The data analysis technique used is multiple linear regression analysis. The results of data analysis partially show that only DER has a significant negative impact on DPR. Simultaneously, six independent variables have a substantial effect on the DPR. The coefficient of determination test results shows the Adjusted R Square number of 0.108, which means 10.8% of the variation from the DPR of manufacturing companies, which can be explained by the independent variables used. The remaining 89.2% is caused by other factors such as Growth Opportunity, Ownership, Current Ratio, and others. Â